The Development of Global Citizenship Through Intercultural Virtual Exchange (IVE): A Systematic Literature Review - Wahyu Pambudi; Diana Trisnawati (Keraton: Journal of History Education and Culture, 2024)
This systematic literature review (SLR) investigated the role of Intercultural Virtual Exchange (IVE) in the development of global citizenship among students. Drawing on 22 studies published between 2003 and 2022, the review synthesizes findings related to the impact of IVE on intercultural competence, global awareness, and key skills such as empathy, intercultural communication, and critical thinking. The analysis reveals that IVE offers a flexible and sustainable platform for fostering cross-cultural understanding and collaboration. However, it also highlights several challenges, including technological disparities, language barriers, and issues with pedagogical alignment, which may impede its effectiveness. The review emphasizes the significance of a well-structured curriculum, targeted educator training, and the integration of appropriate technological tools to enhance IVE outcomes. Furthermore, it identifies gaps in the literature regarding student attitudes towards IVE, necessitating further research into factors such as motivation, cultural sensitivity, and prior knowledge. The findings suggest that a comprehensive, interdisciplinary approach, involving educators, technology experts, and intercultural specialists, is crucial for optimizing the implementation of IVE. This review provides valuable insights into the current state of IVE research and offers practical recommendations for future research and practice in the field of intercultural education and global citizenship development.